(untitled) (Biological Sciences - PJSIR, 1996)
Effect of varying levels of nitrogen and plant spacing on growth and green fodder yield of Mott elephant grass tPennisetum purpurem Schum.) was studied under field conditions at Faisalabad. Experimental treatments comprised nitrogen levels, viz., 0, 100 and 200 kg N ha’ and plant spacing, viz., 45 x 45, 60 x 60, 75 x 75 and 90 x 90 cm. Experiment was laid out in a split plot design. In all cuttings, application of nitrogen significantly increased plant height, number of tillers stool’, fresh weight stool·I , crop growth rate and green fodder yield ha’ over control. Similarly an increase in plant spacing significantly increased number of tillers stool’ , fresh weight stool" and crop growth rate, but it caused a significant reduction in green fodder yield. On the basis of three-cutting average data, crop grown at 45 x 45 em and fertilized @ 200 kg N ha’ gave significantly maximum green fodder yield (90.88 t ha") per cutting while crop raised at 90 x 90 em and without N fertilization produced minimum green fodder yield (37.21 t ha’ )